ISLAM AND INCLUSIVE PRINCIPALS' LEADERSHIP STRATEGIES FOR INCLUSIVE TEACHERS - Nina Agustina; Arfiah Arfiah; Rismita Rismita; Mabrouk Chibani Mansouri (Jurnal Asy-Syukriyyah, 2026)
Previous research on inclusive education in Indonesian primary schools has largely concentrated on policy execution and classroom-level practices, while the leadership dimension—particularly when viewed through Islamic and inclusive lenses—has not been explored extensively. This study seeks to analyze how school principals design and implement leadership strategies to strengthen teacher professionalism in educating students with special needs (ABK). A qualitative descriptive approach was employed, with data collected through observations, in-depth interviews, and documentation at SD Negeri Poris Pelawad 5, Tangerang City. The findings demonstrate that leadership characterized by inclusivity and ethical values substantially supports teacher development through structured coaching, continuous professional training, academic supervision, and collaborative practices. Key supporting factors include institutional commitment and policy alignment, whereas constraints involve limited infrastructure, insufficient special assistant teachers, and gaps in teacher understanding of inclusive education. This study contributes conceptually to Islamic educational leadership discourse and offers practical recommendations for improving inclusive education through sustainable professional development and institutional reinforcement.